1996
DOI: 10.1074/jbc.271.51.33123
|View full text |Cite
|
Sign up to set email alerts
|

The Light Chain Subunit Is Required for Clathrin Function in Saccharomyces cerevisiae

Abstract: Clathrin, a multimeric protein involved in intracellular protein trafficking, is composed of three heavy chains (Chc) and three light chains (Clc). Upon disruption (clc1⌬) of the single Clc-encoding gene (CLC1) in yeast, the steady state protein levels of Chc decreased 5-10-fold compared with wild type cells; consequently, phenotypes exhibited by clc1⌬ cells may result indirectly from the loss of Chc as opposed to the absence of Clc. As an approach to directly examine Clc function, clc1⌬ strains were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 33 publications
7
82
0
4
Order By: Relevance
“…The structure showed that the molecules in the asymmetric unit were trimeric, but threefold symmetry was disturbed (68). This observation supports previous findings that CLC contributes to the net stability of trimeric clathrin (69)(70)(71).…”
Section: Clathrin Detrimerization and Nuclear Localizationsupporting
confidence: 80%
See 1 more Smart Citation
“…The structure showed that the molecules in the asymmetric unit were trimeric, but threefold symmetry was disturbed (68). This observation supports previous findings that CLC contributes to the net stability of trimeric clathrin (69)(70)(71).…”
Section: Clathrin Detrimerization and Nuclear Localizationsupporting
confidence: 80%
“…Additional work will be needed to sort out whether the position of helix 7j depends at all on the C-terminus of CLC. The fact that CLC knockouts in Saccharomyces cerevisiae destroy the trimeric clathrin structure (70,71), while the clathrin structure in Dicytostelium is unaffected by knocking down CLC (73), suggests that any CLC role will likely be organism specific.…”
Section: Clathrin Detrimerization and Nuclear Localizationmentioning
confidence: 99%
“…In yeast cells, clathrin, actin, and BAR proteins contribute to vesicle formation in different capacities. Though the inhibition of actin polymerization completely arrests endocytosis (9,11,12,14), the absence of clathrin and BAR proteins only leads to ∼50% and 25% reduction in the internalization events, respectively (14)(15)(16)(17)(18). Although a high scission rate is maintained in BAR mutant cells, there is a fundamental difference between the shape evolution process in these and the wild-type cells.…”
Section: Bar Proteinsmentioning
confidence: 92%
“…The CLC exists in two isoforms, LCa and LCb. These appear to be randomly recruited to clathrin triskelia and are believed to be involved in CHC trimerization (Chu et al, 1996;Huang et al, 1997).…”
Section: Clathrinmentioning
confidence: 99%